Cord blood vitamin A and vitamin D levels in relation to physical growth in exclusively breastfed infants aged 0-6 months - Zhao, Wei; Li, Chao; Shen, Wen Zhi; Li, Kai Yun; Cai, Yi Xi; Li, Feng; Fu, Hong; Peng, Bin; Chen, Jie; Li, Ting Yu; Chen, Li (Frontiers in Endocrinology, 2024)
Background: Vitamins A and D are essential for the health of pregnant women and infants. Nevertheless, the relationship between umbilical cord blood vitamins A and D levels and the physical growth of exclusively breastfed infants remains uncertain. Objective: This cohort study aims to examine the relationship between cord blood vitamins A and D levels and the physical growth of exclusively breastfed infants aged 0-6 months. Methods: 140 singleton mother-infant pairs were recruited in total. Questionnaires were used to collect maternal and infant information, and liquid chromatography was utilized to quantify the levels of vitamins A and D in the umbilical cord blood.Anthropometric measurements were conducted at birth, at 3 and 6 months of age, and the weight-for-age z-score (WAZ), length-for-age z-score (LAZ), head circumferencefor-age z-score (HAZ), and BMI-for-age z-score (BMIZ) were calculated. Univariate and multivariate linear regression models were used for the analysis. Results: The average concentration of vitamins A and D in cord blood was 0.58 ± 0.20 μmol/L and 34.07±13.35 nmol/L, both below the normal range for children. After adjusting for confounding factors, vitamin A levels in cord blood positively correlated with HAZ growth in infants aged 3–6 months (β= 0.75, P < 0.01) while vitamin D levels negatively correlated with LAZ growth (β= −0.01, P = 0.01) and positively correlated with BMIZ growth (β= 0.02, P < 0.01). Conclusion: Higher Vitamin A levels at birth promote HAZ growth in infants aged 3–6 months while higher vitamin D levels at birth promote BMIZ growth in infants aged 3–6 months.